Asymptotic automorphism groups of Cayley digraphs and graphs of abelian groups of prime-power order - Dobson, Edward (Ars mathematica contemporanea, 2010)
We show that almost every Cayley graph ?$Γ$? of an abelian group ?$G$? of odd prime-power order has automorphism group as small as possible. Additionally, we show that almost every Cayley (di)graph ?$Γ$? of an abelian group ?$G$? of odd prime-power order that does not have automorphism group as small as possible is a normal Cayley (di)graph of ?$G$? (that is, ?$G_L \triangleleft {\rm Aut}(Γ))$?.
Keywords: grupe; matematika; teorija grafov